Conflict Resolution and Crisis Communication. Transforming Conflicts and Building Peace (2nd edition) - HERȚA, Laura-Maria; POP-FLANJA, Delia (Presa Universitară Clujeană, 2023)
This volume aims to bring together articles which present, explore, analyse and interpret salient events from the international arena. The focus falls on those phenomena and events which have a global outreach and which impact entire communities, as well as individuals and domestic/sub‐state groups. Traditionally, the analysis of international politics used to evoke a Realist view and mind‐set and, starting with the 1970s, a Neorealist outlook, according to which phenomena occurring in world politics generated reactions from state actors and, hence, state interaction and state behaviour were observed and commented on.